Parents' Working Conditions in the Early COVID-19 Pandemic and Children's Health-Related Quality of Life: The Ciao Corona Study - Nevesthika Muralitharan; Nevesthika Muralitharan; Gabriela P. Peralta; Sarah R. Haile; Thomas Radtke; Agne Ulyte; Milo A. Puhan; Susi Kriemler (Frontiers Media S.A., 2022)
Objective: To assess the associations between parents' working conditions during the lockdown period (March-May 2020) and children's health-related quality of life (HRQOL) over the first year of the COVID-19 pandemic in Zurich, Switzerland.Methods: We included 2211 children (6-16 years) and their parents from the prospective study Ciao Corona. Parents reported their employment status and working conditions during the lockdown. Children's HRQOL was assessed in June-July 2020, January and March 2021 using the parents-report of the KINDL®. We used mixed models to assess the associations between parents' working conditions and children's HRQOL at the three time points.Results: Children from families in which at least one parent changed their working conditions during the lockdown showed lower HRQOL in June-July 2020, than children from families in which neither parent experienced changes. Children from families in which at least one parent had to work remotely continued to show lower HRQOL in January and March 2021.Conclusion: Changes in parents' working conditions during lockdown were negatively associated with children's HRQOL. Public health policies aiming to support families susceptible to adverse changes are needed.